IMPLEMENTASI PEMBELAJARAN TALAQQI DI SEKOLAH TAHFIZH PLUS KHOIRU UMMAH PANDAAN (Metode Pembelajaran dan Tahfidh) - Zahrotul Aini (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2019)
This is research use two the methode is a tallaqqi lafadz methode is the teacher deals directly with the students and maintains the teacher’s reading and prosess it to the child so that the reading is correct, this methodis used Tahfidz and tahsin. While talaqqi thought to convey knowledge related by changing understanding conveying perceptions or conveying thought is applied to all subjects.this is done by transferring a set of children’s knowledge so that children gain understanding and make it their own understanding.